From definition to protection: dilemmas and reflections on the right to refuse treatment for patients with mental disorders in Chinese mainland - Li, Xiaofu; Li, Xiaofan (Frontiers in Public Health, 2024)
Background The case of “a multimillionaire who was sent to a psychiatric hospital after an argument with his son” has sparked heated debate in the Chinese mainland. This incident is particularly significant as 2023 marks the 10th anniversary of the implementation of the Mental Health Law of the People's Republic of China. The focus of the ongoing debate, as brought to light by the aforementioned case, is centered on the right to refuse treatment for patients with mental disorders. Methods This paper is a post-hoc study with a systematic analysis of literature and cases. To ascertain the relationship between the right to refuse treatment for patients with mental disorders and the Mental Health Law, the authors identified key information and data from both official government websites and reliable non-governmental information. Result Both literature and practice have proven that the compulsory hospitalization rule under the Mental Health Law is a denial of the right to refuse treatment for patients who are compulsorily hospitalized. In the absence of changes to the law, compulsory hospitalization will inevitably lead to compulsory treatment in the Chinese mainland. Conclusion According to the human dignity and self-determination right established in the Constitution of the People's Republic of China, patients who are compulsorily hospitalized have the right to refuse treatment. In the absence of a change in the law, given that no neutral review mechanism has been established for such patients and their treatment in the mainland, setting up an internal review mechanism is a more feasible way of protecting the right to refuse treatment for patients with mental disorders.